Learning to Request in a Second Language: A Study of Child Interlanguage Pragmatics - Achiba, Machiko (Second Language Acquisition, 2003)
This book examines the acquisition of requests in English by a seven- year-old Japanese girl during her 17-month residence in Australia. The study focuses on the linguistic repertoire available to the child as she attempts to make requests and vary these to suit different goals and addressees. This book helps unravel features of pragmatic development in the child's interlanguage, a subject about which we yet know very little.